Gender in Indonesian Folklore: A Corpus Linguistic Study - Rhubido, Dadang; Yuwana, Setya; Rengganis, Ririe; Savitri, Eka Dian (Proceeding of International Joint Conference on UNESA, 2024)
This research aims to describe diction that reflects gender in Indonesian folklore. The gender of the characters in folklore is visible through the diction used. This research uses a mixed approach, namely combining a quantitative approach and a qualitative approach. This research uses corpus linguistics methods. The research data is in the form of 110 Indonesian folk tales downloaded from the Ministry of Education and Culture's Language and Literature Diversity Laboratory. Based on the use of diction, it is known that (1) the characters in Indonesian folklore are male and female; (2) the use of male characters is more numerous and widespread in Indonesian folk tales than female characters.